An Ergonomically Assessment of Manually Operated Maize Planter for Male Operators - Singh, Saurabh Kumar; Yadav, Rahul Kumar; Kumar, Abhinav (International Journal of Bio-resource and Stress Management, 2023)
A study was conducted at Sam Higginbottom University of Agriculture, Technology and Sciences (SHUATS), Prayagraj, (U.P), India on (2022–23) for ergonomic assessment of manually operated maize planter for male operators. Anthropometric data of age groups operators of (25–28, 29–32, 33–36, and 37–40 years) was determined. Heart rate, oxygen consumption rate, energy expenditure rate, and body part discomfort score of age groups were determined during working on maize planter. Anthropometric data of stature, arm length, standing eye height, knee height, and elbow height, and body mass index were determined for different age groups. Heart rate, oxygen consumption rate, energy expenditure rate, and body part discomfort score were increased when age groups increased at weight sample of seed (1.5 and 2.0 kg). Heart rate, oxygen consumption rate, energy expenditure rate, and body part discomfort score of 25–28 years age groups were found minimum and varied from 92–101 b min-1, 0.36–0.37 l min-1, 8–10.03 kJ min-1, and 20.75–22.02 respectively on working. Heart rate, oxygen consumption rate, energy expenditure rate, and body part discomfort score of 37–40 years age groups were found maximum and varied from 140–143 b min-1, 0.90–0.93 l min-1, 19–20 kJ min-1, and 51.23–53.87 respectively during working operators on maize planter at different weight samples.